Unique Names in China: Insights From Research in Japan—Commentary: Increasing Need for Uniqueness in Contemporary China: Empirical Evidence - Ogihara, Yuji (Frontiers in Psychology, 2020)
By comparing naming practices between China and Japan, I propose three suggestions on Cai et al.'s (2018) Study 2, which examined historical changes in baby names in China. Their study found that the average daily frequencies of Chinese characters used in baby names decreased between 1950 and 2009. The authors concluded that unique names increased for this period and suggested a rise in the need for uniqueness and individualism in China. However, there are three questions that have remained unanswered. First, did the Chinese characters that were used in names indeed become more unique over time? Second, did the number of Chinese characters in names increase over time? Third, did the reading (pronunciation) of names become more unique over time? Answering these three questions would further increase the validity and impacts of the article and contribute to a better understanding of cultural changes in China.